Exploration and application of post-infrared high-temperature infrared stimulated luminescence dating techniques: investigation of marine terrace deposits along the northern San Andreas Fault - Roozeboom, Jennifer Elizabeth (Kansas State University, 2015)
Optically stimulated luminescence (OSL) dating is a relatively new dating method, tangibly introduced in 1985 when Huntley et al. demonstrated the ability to use light-sensitive traps to measure radiation exposure and determine the age of sediment. Quartz and feldspar grains are commonly used for the method, with quartz receiving significantly more attention than feldspars until the past decade. Recent research has improved the practicality of using feldspars as a reliable dosimeter –an appealing notion as the intrinsic properties of feldspars allow them to date older sediment that may lie beyond the reliable range of quartz dosimetry. This work explores and utilizes the contemporary feldspar technique termed post-infrared, high-temperature infrared stimulated luminescence (pIRIR) dating to add to the existing knowledge base of this method, particularly by testing different preheat and measurement temperature combinations. Analysis of the each pIRIR method indicates that the pIRIR signal stimulated at 225°C is more appropriate for dating than the pIRIR signal stimulated at 290°C. Techniques and protocols developed in this work are done so via their application to a marine terrace that is displaced by the San Andreas Fault. Corals from the terrace along the Pacific plate, dated with U-series by Muhs et al. (2002), offer an age estimate. Comparison of the pIRIR ages to the U-series ages yield an underestimation, suggesting the pIRIR method may be more useful as a means of correlating terraces across the fault, than for providing ages of terrace formation.
Keywords: Optically stimulated luminescence; Post-infrared high-temperature infrared stimulated luminescence; Feldspars; San Andreas Fault; Marine terrace; Geology (0372); Plate Tectonics (0592); Sedimentary Geology (0594)